Agriculture in Islam From the Prespective of Economics, Banking & Finance - muhammad ridwan ab.aziz (UTM PRESS, 2012)
the book includes a range of topics, such as agribusiness from the isamic prespective, agriculture as a tool to solve unemployment problem, contracts of agriculture in fiqh muamalat, financing facilities in islamic banks, as wel as the validity of shariah contracts in agriculture financing.